Kapitalizacja odsetek a zakaz anatocyzmu - Balcerowiak, Przemysław (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
In the article the issue of the institution of interest capitalization with ban on anatocism has been looked into. Turning to the institution of the capitalization of interest, their legal nature has been outlined, showing therefore the duality of the presented side benefit. Given the following division of interest, the capitalization of equity and default interest have been separately delineated.Concerning the issue of the capitalization of equity, an attempt has been made to clarify the legal basis of charging interest. In addition, it has proven necessary to clarify doubts related to the maturity of the claims in the case of periodic interest capitalization.Whereas in the case of default interest, the legal notion of delay has been outlined, also explaining concerns about Article 481 § 1 of the Civil Code. Furthermore, the issue of its legal nature has been decided by indicating whether it should be classified as ius dispositivum, or perhaps, as ius cogens.Ban on anatocism cannot be discussed without addressing the doubts raised concerning its scope, namely whether it applies exclusively to default interest, or also to equity interest. An essential element in this discussion is to present the essence of derogation from ban on anatocism. Firstly, after the formation of arrears, parties may agree to capitalize the interest. Another exception refers to the concept of long-term loans granted by credit institutions. This formulation requires a thorough explanation: first, of the concept of long-term loans and then, of credit institutions. The third exception nis instituting legal action, in which it is legal proceedings that are the most questionable matter, from which it is possible to enforce the capitalized interest.Given the current legal regulation, it should be noted that it is not sufficient to resolve doubts concerning the normative character of the institution of interest capitalization with ban on anatocism. Such reasoning leads to suggest further proposals de lege ferenda.
Keywords: odsetki; kapitalizacja; anatocyzm; wierzytelności; dług